2019
DOI: 10.1149/2.0141915jes
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured LaFeO3 Photocathodes with Onset Potentials for the Hydrogen Evolution Reaction Over 1.4 V vs. RHE

Abstract: The photoelectrochemical properties of phase-pure LaFeO 3 (LFO) nanostructured films are investigated upon modification with a thin TiO 2 film and Pt nanoparticles as a catalyst. LaFeO 3 with crystallite domains in the range of 60 nm are prepared by thermolysis of an ionic-liquid precursor and subsequently deposited onto FTO electrode by spin-coating. Deposition of a TiO 2 layer by solutionbased methods leads to the formation of a heterojunction, attenuating dark current associated with hole-transfer (water ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…31 However, recent efforts have been made to reduce this effect for LFO lms by incorporating a thin TiO 2 hole blocking layer. 38 PEC measurements of all the LFO samples exhibit a large dark current at potentials below +0.4 V RHE . This can be attributed to oxygen reduction on the areas of exposed FTO 48 and on LFO.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…31 However, recent efforts have been made to reduce this effect for LFO lms by incorporating a thin TiO 2 hole blocking layer. 38 PEC measurements of all the LFO samples exhibit a large dark current at potentials below +0.4 V RHE . This can be attributed to oxygen reduction on the areas of exposed FTO 48 and on LFO.…”
Section: Resultsmentioning
confidence: 93%
“…31 Recent work has been done in avoiding this detrimental hole transfer to the electrolyte in LFO lms by incorporating a TiO 2 blocking layer. 38 It is also important to consider the role that the thickness of LFO lms have on PEC properties. For instance, it has been shown that with increasing lm thickness, a shi from oxidative to reductive behavior is observed due to differing band offsets.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, holes can accumulate at the semiconductor/electrolyte interface and take part in the oxygen evolution reaction (OER), increasing majority carrier losses. To combat this a hole‐blocking layer could be employed . Despite this observed vast reduction in photocurrent on purging the electrolyte with N 2, we were able to detect H 2 over a 6 h period with constant light illumination (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…Band alignment of GFO band edges with respect to common electron transport layer (ETL) [44] and hole transport layer (HTL). [44] Band offset with other Fe-based photoelectrodes including LaFeO 3 (LFO), [16] YFeO 3 (YFO), [17] BiFeO 3 (BFO), [45] CaFe 2 O 4 (CaFO), [46] CuFeO 2 (CuFO), [47] ZnFe 2 O 4 (ZFO), [48] and Fe 2 O 3 [49] illustrates how positive is the VBM in GFO. where W is the width of the space charge region, and L n is the holes diffusion length.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9 ] Other ferrite photoanodes include ZnFe 2 O 4 , MgFe 2 O 4 , and CuFe 2 O 4 , achieving external quantum efficiency values of close to 10% and photocurrent onset potentials ranging from 0.6 up to 1 V. [ 10,11 ] Ferrite photocathodes such as LaFeO 3 and YFeO 3 have shown very interesting photovoltages for the hydrogen evolution reaction, but their activity is limited by bulk and surface recombination losses. [ 12–17 ] Ferroelectric materials such as BiFeO 3 and Bi 2 FeCrO 6 show complex PEC properties that have been linked to ferroelectric domains. [ 18,19 ] For instance, BiFeO 3 exhibits both n‐ and p‐type conductivity, including above photovoltages larger than the bandgap.…”
Section: Introductionmentioning
confidence: 99%